ANALISIS PENENTUAN LOKASI OPTIMAL UNTUK IBU KOTA PADA CALON DAERAH OTONOMI BARU KABUPATEN BANYUMAS BARAT - Toriqo Gusniar Ramadhan; Purnomo Adi Saputro; Rahma Hayati; Wahid Akhsin Budi Nur Sidiq (Universitas Negeri Semarang, 2025)
Banyumas Regency will be divided into 3 new autonomous regions: Banyumas Regency, West Banyumas Regency, and Purwokerto City. As a prospective new autonomous region, West Banyumas Regency requires a strategic capital city location. This research aims to: (1) Identify the availability of public service facilities; (2) Measure the level of accessibility; (3) Identify strategic geographical conditions and locations for the potential capital city; and (4) Determine the most optimal location for the capital city of West Banyumas Regency. This research employs a quantitative research approach with a survey research type. The population in this study includes all sub-districts that will be part of the prospective new autonomous region (CDOB) of West Banyumas Regency. The results of the research indicate Ajibarang and Wangon Sub-districts as candidate capital cities, as they possess the most complete range of facility types in CDOB West Banyumas. Ajibarang Sub-district obtained a higher accessibility score compared to Wangon Sub-district, with a ratio of 8:2, and also has a better strategic location score based on the Konig-Shimbell analysis due to its lower connectivity value. Meanwhile, Wangon Sub-district only excels in its geographical condition due to its extensive lowland area. Overall, Ajibarang Sub-district is considered more optimal to become the capital city location of CDOB West Banyumas Regency as it excels in 3 out of the 4 analyzed aspects.